Stigma Komunikasi Negatif pada Pasien ODHA (orang dengan HIV dan AIDS) Yayasan Medan Plus di Kota Medan - Alexsander Giawa; Nina Siti Salmaniah Siregar; Nadra Ideyani Vita (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2022)
The title of this research is Public Stigma of Negative Communication on ODHA Patients (people with HIV and AIDS) Yayasan Medan Plus in Medan (a qualitative descriptive study of the impact of public stigma of negative communication for ODHA patients, Yayasan Medan Plus in Medan). The theory used in this research is the theory of Josep A Devito, the theory of stigma by Erving Goffmen, the theory of beliefs, values and attitudes. This research uses descriptive qualitative method. The informants in this study were 11 people, of which 6 were ODHA patients, 9 people with HIV and AIDS and 5 people are the citizens of Medan. Data collection techniques are in-depth interviews, observation, literature study and documentation. The results of this study are the communication stigma given by the community to ODHA patients (people with HIV and AIDS). The effect of continuous communication given by the people of the city of Medan to patients living with HIV (people with HIV and AIDS) at the Yayasan Medan Plus in the city of Medan.